Cation Template‐Assisted RAFT Cyclopolymerization of Hexa(Ethylene Glycol) Di(meth)acrylates to Thermoresponsive Pseudo‐Crown Ether Polymers. Issue 18 (27th April 2021) - Kimura, Yoshihiko; Terashima, Takaya
Abstract: Cation template‐assisted reversible addition fragmentation/chain transfer (RAFT) cyclopolymerization of hexa(ethylene glycol) diacrylate (PEG6DA) or hexa(ethylene glycol) dimethacrylate (PEG6DMA) is developed as a versatile system to produce large in‐chain ring cyclopolymers, thermoresponsive pseudo‐crown ether polymers. For an efficient synthesis, potassium hexafluorophosphate (KPF6 ) is employed as a cation template; PEG6DA as well as PEG6DMA recognizes the potassium cation with the hexa(ethylene glycol) spacer to dynamically form a pseudo‐cyclic divinyl monomer. Those monomers interacting with the potassium cations are efficiently polymerized with RAFT agents and radical initiators into cyclopolymers comprising 24‐membered hexa(ethylene glycol) rings. The cation template‐assisted RAFT cyclopolymerization is also effective for the synthesis of amphiphilic random cyclocopolymers bearing hydrophilic hexa(ethylene glycol) rings and hydrophobic butyl groups. Cyclopolymers of PEG6DA and PEG6DMA further show thermoresponsive solubility in water. The cloud point temperature of cyclopoly(PEG6DA)s is higher than that of a cyclopoly(PEG6DMA). Abstract : Cyclopolymers comprising large 24‐membered poly(ethylene glycol) rings are synthesized by cation template‐assisted reversible addition fragmentation/chain transfer cyclopolymerization of hexa(ethylene glycol) diacrylate or dimethacrylate. Efficient cyclopolymerization is achieved by using a potassium template that induces a dynamic formation of pseudo‐cyclic monomers. The cyclopolymers serve as thermoresponsive pseudo‐crown ether polymers in water.